2021
DOI: 10.1186/s13293-021-00400-4
|View full text |Cite
|
Sign up to set email alerts
|

In search of sex-related mediators of affective illness

Abstract: Sex differences in the rates of affective disorders have been recognized for decades. Studies of physiologic sex-related differences in animals and humans, however, have generally yielded little in terms of explaining these differences. Furthermore, the significance of these findings is difficult to interpret given the dynamic, integrative, and highly context-dependent nature of human physiology. In this article, we provide an overview of the current literature on sex differences as they relate to mood disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 307 publications
1
5
0
Order By: Relevance
“…Thus, the levels of these genes were either increased in the dorsolateral prefrontal cortex and subgenual anterior cingulate cortex or decreased in the amygdala of men with MDD, whereas, in women with MDD, these effects were opposite (reduced expression in the dorsolateral prefrontal cortex and subgenual anterior cingulate cortex but increased expression in the amygdala) [100]. These data show the opposite molecular signatures of MDD in men and women, which is consistent with the sex-specific changes in incidence, symptomatology, and neuroimaging in MDD patients [103].…”
Section: Human Studiessupporting
confidence: 80%
“…Thus, the levels of these genes were either increased in the dorsolateral prefrontal cortex and subgenual anterior cingulate cortex or decreased in the amygdala of men with MDD, whereas, in women with MDD, these effects were opposite (reduced expression in the dorsolateral prefrontal cortex and subgenual anterior cingulate cortex but increased expression in the amygdala) [100]. These data show the opposite molecular signatures of MDD in men and women, which is consistent with the sex-specific changes in incidence, symptomatology, and neuroimaging in MDD patients [103].…”
Section: Human Studiessupporting
confidence: 80%
“…From our data, it seems that men could be less susceptible to psychological symptoms like anxiety, PTSD or insomnia. Previous research has identified several domains that could explain this gender differences between men and women in psychological symptoms, including brain structure, network connectivity, signal transduction, transcription/translation, epigenetic changes, and hormonal changes during life course 40 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The risk of stress‐dependent psychopathology differs markedly between the sexes, with women more than twice as likely to develop depression and anxiety disorders (Hantsoo & Epperson, 2017; Kessler, 1997; Olff, 2017; Verma et al, 2011), and displaying more severe symptoms (de Graaf et al, 2002). Distinct (in some cases opposing) neurobiological changes are reported in men and women with stress‐related major depressive disorder (MDD), supporting unique mechanisms of disease in males and females (Seney et al, 2018; Sikes‐Keilp & Rubinow, 2021). Experimental animal studies also identify opposing neurobiological and behavioral responses to social stress in females and males (Oliver et al, 2020; Rivera‐Irizarry et al, 2020).…”
Section: Introductionmentioning
confidence: 99%